Menopause. - García La Madrid, Martín (2015)
The topic that I discuss is applicable to menopause, which falls under the heading of menopause, which we consider as an endocrine and vegetative crisis that accompanies sexual decline of women. Menopause means the cessation of the rule, ie the disappearance of one of the symptoms or manifestations of female sexual life. In other words we consider menopause as a momentary external or characteristic phenomenon, while menopause is a fundamental phenomenon and deep around the body and represents a large time span.